Continuing Professional Development Participation, Perceived Institutional Support, and Burnout Among Secondary School Teachers: A Structural Equation Modelling Approach - Try Mahendra Siregar; Rahmat Sapaat Siregar (Barkah Publishing, 2026)
Teacher burnout has intensified internationally, with secondary school teachers reporting sustained overload, emotional strain, and reduced professional efficacy. While workload and classroom demands are established antecedents, less is known about how teachers’ continuing professional development (CPD) participation especially in forms that are collaborative and practice-embedded relates to burnout when teachers’ perceived institutional support (PIS) is considered. This study examined the relationships between CPD participation, perceived institutional support, and burnout (emotional exhaustion, depersonalisation, and reduced personal accomplishment) among secondary school teachers, drawing on the Job Demands–Resources (JD–R) model and organisational support theory. A cross-sectional survey was administered to 210 secondary school teachers. Measures included the Maslach Burnout Inventory–Educators Survey (MBI ES), a CPD engagement scale capturing formal, informal, and collaborative CPD participation, and an adapted Perceived Organisational Support measure (Eisenberger et al.). Data were analysed using PLS SEM in SmartPLS 4. Measurement model evaluation included indicator reliability, internal consistency (CR), convergent validity (AVE), and discriminant validity checks. Structural paths were assessed using bootstrapping, effect sizes (f²), and predictive relevance indicators. The measurement model demonstrated acceptable reliability and convergent validity. Structural results indicated that perceived institutional support was negatively associated with emotional exhaustion and depersonalisation, and positively associated with personal accomplishment. CPD engagement showed a small direct association with reduced burnout, with stronger links evident for collaborative CPD. Additionally, perceived institutional support partially mediated the relationship between CPD engagement and burnout dimensions. Findings suggest that CPD is most protective against burnout when embedded in supportive institutional conditions. Policy and school leadership should treat CPD and institutional support as coupled resources designed to build instructional capacity while also buffering chronic strain.